Improving Investment Decisions with Simulated Experience - Bradbury, Meike A. S.; Hens, Thorsten; Zeisberger, Stefan (Review of Finance, 2015)
Abstract We apply a new and innovative approach to communicating risks associated with financial products that should support investors in making better investment decisions. In our experiments, participants are able to gain “simulated experience” by random sampling of a previously described return distribution. We find that simulated experience considerably improves participants’ understanding of the underlying risk–return profile and prompts them to reconsider their investment decisions and to choose riskier financial products without regretting their higher risk-taking behavior afterwards. This method of experienced-based learning has high potential for being integrated into real-world applications and services.